췌관-공장 문합술에서 흡인형 췌관 스텐트의 초기 결과 보고 - 안영준(Young Joon Ahn); 황기태(Ki-Tae Hwang); 허승철(Seung-Chul Heo); 정인목(In Mok Jung); 정중기(Jung Kee Chung); 장진영(Jin-Young Jang); 김선회(Sun-Whe Kim) (Annals of surgical treatment and research, 2007)
Purpose: We wanted to evaluate the feasibility of using the suction pancreatic duct stent, which was designed to aspirate pancreatic fluid more actively around the pancreaticojejnostomy site during performance of pancreaticoduodenectomy for preventing pancreatic fistula. Methods: In 7 consecutive pancreaticoduodenectomy patients, we inserted a PVC tube into the remnant pancreatic duct across the duct-to-mucosa type pancreaticojejunostomy at a 2 cm depth as a totally external pancreatic stent. This stent was connected with the aspiration bag of a Jackson- Pratt drain for generating negative pressure. We inserted another Jackson-Pratt drain beneath the pancreaticojejunosomy site and checked the amylase level in the body fluid and the serum at the postoperative 1st and 5th days for evaluating pancreatic leakage. We also checked the daily amount of pancreatic fluid obtained through the suction stent. Pancreatic fistula was defined as an amylase level in the body fluid ＞10,000 U/L on postoperative 1 day or an amylase level in the body fluid ＞3 times the serum amylase level on the postoperative 5th day. Results: On postoperative day 1, the mean level of intraabdominal fluid amylase was 1,404 U/L (355～3,850 U/L). On the postoperative 5th day, the mean level of amylase in the body fluid was 40.3 U/L (12～144 U/L) and the mean level of serum amylase was 38.3 U/L (19～71 U/L). Even on the postoperative 1st day, we could collect a considerable amount of pancreatic fluid (mean: 55.6 ml (range: 9～169 ml)). There was no complication associated with pancreatic leakage. Conclusion: The suction pancreatic stent can be a feasible method to prevent pancreatic leakage. Additional randomized studies to compare the conventional pancreatic duct stent with the suction pancreatic duct stent are mandatory. (J Korean Surg Soc 2007;72:478-482) KCI Citation Count: 0